2006
DOI: 10.1080/14767050600852171
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous inhibitors of nitric oxide and preeclampsia: A review

Abstract: Nitric oxide (NO) is a potent vasodilator. NO is synthesized by NO synthases (NOS) and NOS are inhibited by asymmetrical dimethylarginine (ADMA). ADMA is metabolized by dimethylarginine dimethylaminohydrolase (DDAH) and excreted in the kidneys. Lower ADMA levels in pregnant women compared to non-pregnant controls suggest that ADMA has a role in vascular dilatation and blood pressure changes. Several studies show an increase in ADMA levels in pregnancies complicated with preeclampsia. Elevated ADMA levels in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Moreover, elevated ADMA levels have been found in preeclampsia before the appearance of clinical signs, which might diminish NO bioavailability to a greater extent [12] (Fig. 1).…”
Section: Adenosine L-arginine and No (Alano) Pathwaymentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, elevated ADMA levels have been found in preeclampsia before the appearance of clinical signs, which might diminish NO bioavailability to a greater extent [12] (Fig. 1).…”
Section: Adenosine L-arginine and No (Alano) Pathwaymentioning
confidence: 98%
“…In the endothelium, this gas is primarily, if not exclusively, synthesized from the semi-essential cationic amino acid Larginine by endothelial NO synthase (eNOS), and this synthesis can be inhibited naturally by asymmetrical dimethylarginine (ADMA) [12]. Alterations in the synthesis and/or biological actions of NO have been related to abnormal blood flow in disorders of pregnancy that present as different entities but appear to share a common origin: the presence of placental endothelial dysfunction.…”
Section: Endothelial Dysfunction In the Placenta And Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The released amounts are sufficient to inhibit endogenous NO production. Recent clinical and experimental investigations have indicated that ADMA is both a strong marker and a mediator of many aspects of endothelial dysfunction syndrome, including not only cardiovascular and renal diseases but also preeclampsia [3][4][5][6]. At present, little information is available about the potential physiological roles of ADMA in a perinatal setting.…”
Section: Introductionmentioning
confidence: 95%
“…Elevated ADMA levels in preeclampsia are detected before clinical symptoms develop; hence these findings suggest that ADMA may play a role in the pathogenesis of preeclampsia (Slaghekke et al, 2006).…”
Section: Discussionmentioning
confidence: 95%